Characteristics of the Ugandan rice varieties grown in the Rostov region - P. I. Kostylev; E. V. Krasnova; A. V. Aksenov (Зерновое хозяйство России, 2021)
Rice is a valuable agricultural crop that is used as food for more than half of the world's population. The development of highly productive varieties and hybrids with high product quality assumes the utilization of new initial material from different countries in the breeding process. The purpose of the current research was to conduct an ecological testing of the rice varieties from Uganda in the Proletarsky district of the Rostov region in Russia and use them in the breeding process. There were studied the Ugandan rice samples ‘Nerica 1’, ‘Nerica 4’, ‘Komboka’, ‘Wita 9’, ‘Namche 1’, ‘Namche 2’, ‘Namche 3’, ‘Namche 4’, ‘Namche 5’, ‘Namche 6’ (NaCRRI) in comparison with the Russian variety ‘Komandor’ (FSBSI “ARC “Donskoy”). The study of the Ugandan rice varieties according to a number of economically valuable traits and biological properties showed that the vegetation period from soil flooding to rice maturing took 100–113 days, the standard variety ‘Komandor’ needed 83 days. The varieties ‘Komboka’ and ‘Wita 9’ did not bear blossom. All samples had a short habit, with 63-95 cm of plant height. The long drooping panicles of 18.5–22.3 cm carried from 122 to 213 seeds. The caryopses were elongated, the length of the caryopses varied from 9.0 to 9.5 mm, and the width ranged from 2.7 to 3.1 mm. 1000 seed weight varied from 26 to 34 g, number of seeds per panicle ranged from 122 to 213 pieces. Genetic analysis of the second generation hybrids ‘Kontakt × Nerica 1’ and ‘Boyarin × Nerica 4’ showed different types of traits’ inheritance, from negative dominance (vegetation period) through the absence of dominance (caryopses size) to overdominance (plant height, seed weight per panicle and number of seeds per panicle).